An overview of the gender gap in the European region - Mouronte López, Mary Luz (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The study of the gender gap has attracted the interest of international organizations and researchers. This paper provides an overview of the situation of women in Europe. The research is carried out on the basis of gender variables located in international repositories and using data analysis techniques. The situation in Europe is positive but improvements are needed in some countries in areas such as business, law and politics. Women in some countries would also benefit from actions to redress discrimination in the family sphere.